The assessment of a world-ranked wheelchair sprinter aerodynamics analysis by computer fluid dynamics - Forte, P. (Universidade da Beira Interior, 2018)
Aerodynamics can play an important role in the performance of a wheelchair spinter.The aim of this thesis was to analyse the aerodynamics of a wheelchair sprinter by computer fluid dynamics. This thesis comprises a series of four studies (a review of the literature and three empirical studies).The studies aimed to:(i) review the literature on aerodynamics in wheelchair racing; (ii) compare two different helmets (road vs time trial) at severalpeeds and head positions by CFD. (iii) assess the aerodynamics in different key-moments of the stroke cycle by CFD; (iv)compare the mechanical power and energy cost of transportation delivered by an elite wheelchair sprinter in key-moments of the stroke cycle.The main conclusions were: (i) there is a lack of research on wheelchair racing aerodynamic`s assess by CFD; (ii) a time trial helmet imposed lower drag keeping a neck hyperextension; (iii) the aerodynamics of a wheelchair racing athlete varied over the different phases of the stroke cycle; (iv) the mechanical power and energy cost in elite wheelchair racing varied in different phases of the stroke cycle. The main conclusion of this thesis was that it is possible to enhance the aerodynamics of a wheelchair sprinter by selecting the best sport garement and equipment, as well as keeping a good body alignment in the key-phases of the stroke cycle.